Lipodystrophy syndrome in HIV-infected children on HAART - Steve Innes; Leon Levin; Mark Cotton (AOSIS, 2009)
Lipodystrophy Syndrome (LD) is common in HIV-infected children, particularly in those taking Didanosine, Stavudine, or Zidovudine. Lipoatrophy in particular causes major stigmatization and interferes with adherence. In addition, LD may have significant long-term health consequences, particularly cardiovascular. Since the stigmatizing fat distribution changes of LD are largely permanent, the focus of management remains on early detection and arresting progression. Practical guidelines for surveillance and avoidance of LD in routine clinical practice are presented. Diagnosis of LD is described and therapeutic options are reviewed. The most important therapeutic intervention is to switch the most likely offending antiretroviral to a non-LD-inducing agent as soon as LD is recognised. Typically, where lipoatrophy or lipohypertrophy is diagnosed, the thymidine nucleoside reverse transcriptase inhibitor (NRTI) is switched to a non-thymidine agent such as Abacavir (or Tenofovir in adults). Where dyslipidaemia is predominant, a dietician review is helpful, and the clinician may consider switching to a protease inhibitor (PI)-sparing regimen or to Atazanavir.